Pengaruh Disiplin Kerja Terhadap Kinerja Aparatur Desa Di Kantor Desa Nanga-Nangaon : The Influence of Work Discipline on the Performance of Village Apparatus at the Nanga-Nangaon Village Office - Firmansyah, Andrie (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
Every organization, desires that the achievement of organizational activities can be fulfilled optimally. One of the supporting factors for this achievement is the support of employees or staff who work. The support is in the form of employee or staff work results (performance). The purpose of this study is to measure the effect of work discipline as an independent variable (variable X) on the performance of the Nanga-nangaon Village apparatus, Bunta District as a dependent variable (variable Y). This type of research is a qualitative research that is quantified, where the researcher asks several questions to get responses from the respondents. In order to get how much influence work discipline has on the work discipline of the Village apparatus in question, the author uses simple regression analysis. From the test results, it was found that work discipline has a positive effect on the performance of the Nanga-nangaon Village apparatus, Bunta District. This can be seen from the sig. value of 0.002 and tcount> ttable, namely 3.983> 1.771. The discipline variable has an influence of 55%. This means that 55% of the performance of the Nanga-nangaon Village apparatus is determined by work discipline, while 45% is determined by other factors that have not been studied